1981
DOI: 10.1113/jphysiol.1981.sp013998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intestinal secretagogues and distension on small bowel myoelectric activity in fasted and fed conscious dogs

Abstract: SUMMARY1. Defined jejunal segments were perfused with solutions of bile salts and of ricinoleic acid during fasting and after feeding in two groups of conscious dogs, one with the segment in continuity, and the other with a Thiry-Vella loop. Myoelectric activity was recorded from chronically implanted electrodes on the jejunal segment and also from the proximal and distal in situ bowel.2. The results in both groups were identical. During fasting, migrating complexes were present in the segment, but were replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Relax ation of small bowel muscle was reported after exposure to bile acids [24] and Haney et al [25] showed that dilute bile and semipure bile acids (tauro-and glycocholate) reduced the transit time of pellets through canine loops. Furthermore, CDCA was demon strated [26] to abolish MMCs in human duo denum and to interrupt MMCs in the canine jejunum [27], As expected [3,28], highly con centrated CDCA (15 mM) reduced water ab sorption by the ileum. Lower concentrated CDCA (5 mM) did not have such a pro nounced effect on water absorption.…”
Section: Discussionmentioning
confidence: 89%
“…Relax ation of small bowel muscle was reported after exposure to bile acids [24] and Haney et al [25] showed that dilute bile and semipure bile acids (tauro-and glycocholate) reduced the transit time of pellets through canine loops. Furthermore, CDCA was demon strated [26] to abolish MMCs in human duo denum and to interrupt MMCs in the canine jejunum [27], As expected [3,28], highly con centrated CDCA (15 mM) reduced water ab sorption by the ileum. Lower concentrated CDCA (5 mM) did not have such a pro nounced effect on water absorption.…”
Section: Discussionmentioning
confidence: 89%
“…In two dogs which served as controls, the continuity of the small intestine was not disturbed. In three dogs, a 30 cm jejunal T-V loop was constructed by transaction of the intestine 40 cm distal to the ligament of Treitz (Da Cunha Melo, Summers, Thompson, Wingate & Yanda, 1981).…”
Section: Animalsmentioning
confidence: 99%
“…16 Since the extrinsic nerve has been shown to modulate initiation or propagation, or both, of phase 3 contractions in the small bowel, 25 denervation may have influenced the pattern of phase-3-like contractions in the intestinal grafts.…”
Section: Commentsmentioning
confidence: 99%